1997
DOI: 10.1159/000190139
|View full text |Cite
|
Sign up to set email alerts
|

The Transplanted Nephronic Mass Influences Renal Vascular Resistance and Blood Flow of the Kidney Graft

Abstract: In order to assess whether the transplanted nephronic mass plays a role in the progression of chronic graft dysfunction, 83 well-functioning renal transplants were investigated. Plasma creatinine, creatinine clearance, renal volume, blood flow and renal vascular resistance were measured. The weight of the donor was considered as an index of the transplanted renal parenchyma and the weight of the recipient as an index of the required nephronic mass. To evaluate the adequacy of the transplanted nephronic mass, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Kim et al [16] calculated the donor kidney weight to recipient body weight ratio as a measure of nephron mass and found that recipients with a high ratio had better graft function. Others have studied the donor/recipient body weight as an index of transplanted kidney mass [17]. They divided their patients into two groups, those with a donor/recipient weight ratio above and below 1.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [16] calculated the donor kidney weight to recipient body weight ratio as a measure of nephron mass and found that recipients with a high ratio had better graft function. Others have studied the donor/recipient body weight as an index of transplanted kidney mass [17]. They divided their patients into two groups, those with a donor/recipient weight ratio above and below 1.…”
Section: Discussionmentioning
confidence: 99%